Use of Polymeric Energy Absorption Liners to Improve the Concrete Rock Fall Barriers - KÖMÜRLÜ, Eren (GeoScience Engineering, 2021)
In this study, usability of polymer foam coatings on impact surfaces of concrete rock fall barriers to increase the energy absorption capacity performances was investigated with a series of experimental studies. For this purpose, impact tests were carried out on different concrete block samples within the laboratory tests. According to the results, it was determined that the displacement values of the barrier blocks due to the impact effect can be significantly reduced by using polymer energy absorption liners. Additionally, cracks and failures of the concrete block bodies resulting from high impact energies can be prevented by the polymer energy absorption liners. It was assessed that a polyurethane based thermoset foam coating with a density of 60 kg/m3 can economically and remarkably improve the concrete barriers against impact loads. Keywords: Concrete barriers; Energy absorption capacity; Rock fall barriers; Rock falls.